89.6k views
0 votes
Find the inverse of the function below and write it in the formyequals=f Superscript negative 1 Baseline left parenthesis x right parenthesisf−1(x).​(b) Verify the relationshipsf(f^-1(x)) and f^-1(f(x))=x​f(x)=3x+5(a) f^-1(x)=.....

2 Answers

2 votes

The inverse of the function f(x) = 3x + 5 is
f^(-1)(x) = (x - 5)/(3)

How to determine the inverse of the function

From the question, we have the following parameters that can be used in our computation:

f(x) = 3x + 5

Express the function as an equation

So, we have

y = 3x + 5

Swap the occurrence of x and y in the equation

This gives

x = 3y + 5

Subtract 5 from all sides

3y = x - 5

So, we have


y = (x - 5)/(3)

Express as an inverse function


f^(-1)(x) = (x - 5)/(3)


f^(-1)(x) = (x - 5)/(3)

Verifying the relationship
f^(-1)(f(x)) and
f(f^(-1)(x))

We have


f^(-1)(f(x)) = (3x + 5 - 5)/(3)


f^(-1)(f(x)) = (3x )/(3)


f^(-1)(f(x)) = x

Also, we have


f(f^(-1)(x)) = 3 * (x - 5)/(3) + 5


f(f^(-1)(x)) = x - 5 + 5


f(f^(-1)(x)) = x

Hence, the inverse of the function is
f^(-1)(x) = (x - 5)/(3)

Question

Find the inverse of the function below and write it in the form y = f^-1(x)

Verify the relationshipsf(f^-1(x)) and f^-1(f(x))=x​

f(x)=3x+5

User SilverArc
by
5.8k points
1 vote

Answer:

a.
f^(-1)(x)=(x-5)/(3).

b. See below

Explanation:

The given function is:
f(x)=3x+5

To find the inverse function, we let
y=3x+5.

We interchange x and y to obtain:
x=3y+5.

We now solve for y;

First add -5 to both sides of the equation;


x-5=3y.

Divide both sides by 3


(x-5)/(3)=y.

Or


y=(x-5)/(3).

The inverse function is
f^(-1)(x)=(x-5)/(3).

b.

Let us now verify that;


f^(-1)(f(x))=x


\implies f^(-1)(f(x))=(3x+5-5)/(3)


\implies f^(-1)(f(x))=(3x)/(3)


\implies f^(-1)(f(x))=(x)/(1)


\implies f^(-1)(f(x))=x


\boxed{Q.E.D}

User Gdelfino
by
5.7k points